Islamic Religious Education Learning Approach Based on Religious Moderation - Fasyiransyah; Warsah, Idi; Istan, Muhammad (LETIGES, 2025)
This study aimed to investigate the implementation of an Islamic Education learning approach with religious moderation insights at State Senior High School 1 Rejang Lebong, focusing on three aspects: the implementation process, students' attitudes of tolerance, and their responses to the learning approach. The research employed a qualitative case study design involving three Islamic Education teachers and 21 purposively selected students. Data were collected through interviews and observations and then analyzed using an interactive method encompassing data reduction, data presentation, and conclusion drawing. Triangulation ensured data validity through cross-verification between sources and methods. The learning approach integrated values of moderation (tawasuth), tolerance (tasamuh), balance (tawazun), and fairness (ta’adl) into teaching. Group discussions on religious diversity, collaborative projects addressing social issues, and constructivist methods enhanced critical thinking. Teachers facilitated discussions, guided projects, and employed contextual, inclusive materials. Extracurricular activities like interfaith dialogues and community service reinforced classroom lessons. Students displayed tolerance through respectful interactions, diversity acceptance, and fairness in school activities, supported by personal experiences and a harmonious environment. They responded positively, showing enthusiasm, active participation, and a deeper understanding of tolerance and social harmony. This study highlights the importance of integrating religious moderation insights into Islamic Education through inclusive policies, structured activities, and interactive methods to foster tolerance, inclusivity, and social harmony. The research's novelty lies in its comprehensive exploration of the implementation process, students' attitudes, and responses. It offers practical insights into embedding ethical and moderation values in Islamic Education to promote harmony and prevent radicalism.